Inside Chronic Pain : An Intimate and Critical Account - Heshusius, Lous (Book collections on Project MUSE., 2009)
"With Lous Heshusius as a guide, pain patients can learn much about the perils of a modern health-care odyssey. Health professionals can learn how an articulate middle-class female white patient thinks (with all that thinking entails) when her world is irreversibly altered by pain. She does not promise happy endings. Chronic pain is like that. From the rare intersection in this text between patient narrative and physician response, however, readers may construct a dialogue on pain in our time that cannot fail to bring plentiful opportunities for personal insight and professional enlightenment."--The Foreword by David B. MorrisChronic pain, which affects 70 million people in the United States alone-more than diabetes, cancer, and heart disease combined-is a major public health issue that remains poorly understood both within the health care system and by those closest to the people it afflicts. This book examines the experience of pain in ways that could significantly improve how patients and practitioners deal with pain. It is the first volume of a new collection of titles within the acclaimed Culture and Politics of Health Care Work series called How Patients Think, intended to give voice to the concerns of patients about their own medical care and the formulation of health policy. Since surviving a near-fatal car accident, Lous Heshusius has suffered from chronic pain for more than a decade, forcing her to give up her career as a professor of education. Inside Chronic Pain, based in part on the pain journal Heshusius keeps, is a stunning memoir of a life lived in constant pain as well as an insightful and often critical account of the inadequacies of the health care system-from physicians to hospitals and health insurance companies-to understand chronic pain and treat those who suffer from it. Through her own frequently frustrating experiences, she shows how health care providers often ignore, deny, or incorrectly treat chronic pain at immense cost to both the patient and the health care system. She also offers cogent suggestions on improving the quality and outcome of chronic pain care and management, using her encounters with exceptional medical professionals as models. Inside Chronic Pain deals with pain's dramatic and destructive effects on one's sense of self and identity. It chronicles the chaos that takes place, the paralyzing effect of severe pain, the changes in personality that ensue, and the corrosive effects of severe pain on the ability to attend to day-to-day tasks. It describes how one's social life falls apart and isolation takes over. It also relates moments of happiness and beauty and describes how rooting the self in the present is crucial in managing pain. A unique feature of Inside Chronic Pain is the clinical commentary by Dr. Scott M. Fishman, president of the American Pain Foundation. Fishman has long tried to improve the lives of patients like Heshusius. His medical perspective on her very human narrative will help physicians and other clinicians better understand and treat patients with chronic pain